Evaluation of rational drug use based on World Health Organization indicators in a tertiary hospital, Thailand - Anutra Khangtragool; Katemanee Nukompun; Anongnart teeyasuntranonn; Phimwaree Wannasiri; Sittipong Moraray; Waristha Khangtragool (Faculty of Pharmacy, Mahidol University, 2023)
This study aimed to evaluate the rational drug use in a tertiary hospital, Thailand based on World Health Organization (WHO) indicators. This retrospective study was conducted using electronic data from medical records which detailed dispensed prescriptions in the outpatient department (OPD) in a tertiary hospital, Thailand from April 2019 to March 2020. Core rational drug use was determined by the average number of drugs per prescription, percentage of drugs prescribed from the Essential Medicines List (EML) and oral antibiotic consumption using the defined daily dose (DDD). The average number of drugs per prescription in this study was 2.17. The average percentage of the drugs from the national list of essential medicines (NLEMs) in OPD was 66.52%. The DDD from April-September 2019 was 2.51 which increased to 4.61 in the period October 2019-March 2020. In conclusion, this study found the average number of drugs per prescription in outpatients was higher than WHO recommendations. The average percentage of drugs of essential drugs in our study was lower than the expected WHO value. Oral antibiotic consumption measured by DDD had increased. Therefore, policy regarding rational drug use needs to be accelerated as a policy in hospital. Irrational use of medicines is a multidimensional issue and requires interventions at several levels including areas involving health systems, overall organization, doctors, dispensers, patients and community and it remains a challenge in health facilities.